Ways of Knowing: Passionate Humility and Reflective Practice in Research and Management - Yanow, Dvora (American review of public administration, 2009)
For all the attention that the concept of reflective practice has attracted, very little has been said concerning what might incline someone to be open to engage in it. My concern in this essay is with two characteristics of professional, including administrative, practice—a language of certainty and a language of inquiry —and, when the conditions under which the language of certainty has come to dominate professional practice, with the question of what might be required to introduce a posture of reflective inquiry into that practice. I advance the idea that “passionate humility” may be one of the criteria requisite for the cultivation of reflective practice, as it contains the promise of turning administrative and policy action from a language of certainty to a language of reflective inquiry. I suggest that we might learn something about the production and place of humility from the treatment of scientific practice in the philosophy of natural and social science, in two areas: in general, which sees “science” as grounded at least in part in an attitude of doubt; and in particular, from interpretive research methods and interpretive policy analysis, in which the language of inquiry is increasingly operative. Both of these might have something important to tell us concerning contemporary practices in administration and management.